The Implementation of 2013 Curriculum at SMA Negeri 12 Pekanbaru - Sri Yuliani (UIR Press, 2016)
The aim of the research was to find out teaching and learning activities at SMA Negeri 12 in implementing 2013 curriculum. This research was based on the preliminary studies in some Junior and Senior High Schools around Pekanbaru by observing and interviewing the English teacher in excuting 2013 curriculum. The design of this Research was qualitative.The researcher used observation sheet and interview to find out the activities in SMA Negeri 12. Based on the research findings, first, the stage of teaching and learning process in the classroom, the teacher could not implement the step ideally, second, the professional curriculum from the government did not provide the available training to support teaching and learning in the classroom and the last the availability of resources and media were not supported yet. By conducting this research, the researcher hoped that the government conducting the appropriate training to all English teachers in implementing 2013 curriculum.